ANALYSIS OF INVESTMENT SENDITIVITY IN TAMAN MELATI DINOYO APARTMENT, MALANG CITY - Classinta ARD, Bella Astrina; Muhammadun, Haris; Nugroho, Laksono Djoko (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This research investigates the investment potential of Taman Melati Dinoyo Apartment in Malang City, focusing on economic and property market analysis. This research identifies the main factors affecting apartment investment, including property prices, construction costs, occupancy rates, and interest rates. Through a comprehensive literature review and primary data collection through interviews, the research provides insights for property developers, highlighting potential risks and effective mitigation strategies. The proposed investment structure involves a 30% equity and 70% borrowing ratio. Analysis methods such as NPV, IRR, BCR, and Payback Period are used for financial assessment. The Taman Melati Dinoyo Apartment Project in Malang City is financially feasible, with a NJOP value of Rp. 418,462,580,000. The NPV value is positive at Rp. 55,585,691,096, although the IRR is slightly below MARR at -8.99%. The BCR is 0.7997, indicating the project is less than 1, and the payback period is reached in the second year at IDR 186,959,656. Sensitivity analysis showed feasibility even with an increase in investment by 38% and a decrease in revenue by 20%